How do you solve #3x^2 - 6x = 0#?
x = 0 , x = 2
Factorise the left side and equate each of the factors to zero.
By signing up, you agree to our Terms of Service and Privacy Policy
To solve the equation 3x^2 - 6x = 0, you can factor out the common term x:
3x(x - 2) = 0
Then, you set each factor equal to zero:
-
3x = 0 Divide both sides by 3: x = 0
-
x - 2 = 0 Add 2 to both sides: x = 2
Therefore, the solutions to the equation 3x^2 - 6x = 0 are x = 0 and x = 2.
By signing up, you agree to our Terms of Service and Privacy Policy
When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
- How do you rewrite into vertex form #f(x)=4x^2-16x+5#?
- What is the vertex form of #y=3x^2-18x+3#?
- You deposit $5000 in an account that pays 2% annual interest compounded monthly. How much do you have after 5 years?
- How do you solve #x^2+2x-8=0 # using completing the square?
- The sum of three consecutive odd numbers is -21, how do you find the smallest number?
- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7